2013
DOI: 10.1007/s00066-013-0404-4
|View full text |Cite
|
Sign up to set email alerts
|

Second primary malignancies in head and neck cancer patients

Abstract: The examinations revealed a high prevalence of curable stage SPM in HNSCC patients. Adapting a surveillance scheme including a chest CT is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
5
0
3
Order By: Relevance
“…The incidence of a synchronous lung tumor in these cases is 1%, whereas the incidence of a metachronous tumor increases to 10% in patients who have survived ≥3 years (7,10). When the location of primary malignancies was analyzed in the present study, the second most frequent group was respiratory system malignancies with ten cases (22.2%); laryngeal cancer and lung cancer were included in this group.…”
Section: Discussionmentioning
confidence: 63%
“…The incidence of a synchronous lung tumor in these cases is 1%, whereas the incidence of a metachronous tumor increases to 10% in patients who have survived ≥3 years (7,10). When the location of primary malignancies was analyzed in the present study, the second most frequent group was respiratory system malignancies with ten cases (22.2%); laryngeal cancer and lung cancer were included in this group.…”
Section: Discussionmentioning
confidence: 63%
“…[16] Wolff et al showed that CT detected 13 of the 21 histolologically proven diagnosis of SPC with a falsepositive rate of 40.7%. 15 In contrast, Swensen et al…”
Section: Referencesmentioning
confidence: 95%
“…This study demonstrated that performing ENT-endo was recommended as part of systematic evaluation to detect SPC, with overall detection rate of 2.5%. 15 Petit et al reported that in 1560 patients with HNSCC the SPC incidence rate was 3.2% when endoscopy was applied twice annually over a period of 10 years. 16 CT is another method to detect SPC.…”
Section: Referencesmentioning
confidence: 99%
“…Ott et al zeigten nochmals die Äquivalenz einer Dosis von 6 Gy mit einer Dosis von 3 Gy [19]. Danach wurde die in der Leitlinie [2] empfohlene Dosis nach dem ALARA-Prinzip (keep the dose as low as reasonably achievable) auf im Normalfall 3 Gy festgesetzt.…”
Section: Plantare Fasciitis/fersenspornunclassified